Marketing Organic Vegetables in Yogyakarta: Consumers Behavior in Modern Retailers and Community Market - Ismoyowati, Dyah (KnE Life Sciences, 2016)
People’s awareness of their health can be seen with the more and more popular of organic produce including vegetables. Display existed in modern retailers show the rising demand in Yogyakarta. Changing way of how people’s buying from regular to organic ones was influenced by usage of online social media. It is interesting to see how marketing innovation has been done to build customers community using social media by organic and healthy food producers in a community market. Keywords: Behavior, community, market, organic, vegetables.